The Effectiveness of Resolving Money Laundering Cases from Predicate Crime Customs Crimes with Cumulative Indictments - Mutaqin, Fadzal; Waluyo, Bambang (Dinasti Research, 2025)
Corresponding Author: Customs crimes have become increasingly prevalent in Indonesia and have caused significant losses to the state. An effective approach to address this issue is by combining them with money laundering offenses through cumulative charges. The objective of this research is to examine the effectiveness of resolving customs and money laundering cases using cumulative charges. This study adopted a normative juridical method, utilizing the statute approach, the conceptual approach, and the case approach. The research relied on secondary data, which included primary, secondary, and tertiary legal sources. The data were analyzed using a descriptive analysis method. The results of this study showed that, in handling customs crime and money laundering cases, it is more appropriate to use cumulative indictments because this provides several advantages, including establishing customs crime as a predicate crime, recovering state losses, and ensuring effectiveness and efficiency in case resolution in court following the principles of uncomplicated, timely, and affordable justice. This was evidenced by Decision Number 580/Pid.B/2022/PN Btm, which applied cumulative indictments and in which the judge declared the defendant guilty of smuggling and money laundering